Answer:
c. y/2
Explanation:
We can solve this by cross-multiplying.
1. Since
=
, we can cross-multiply both sides of the equation to remove the denominators. Multiple the right side by 2 and the left side by 3 to get 2(x+3)=3(y+2).
2. Distribute to get the x on one side. 2x+6=3y+6.
3. The 6s on both sides cancel out so we are left with 2x=3y.
4. Divide both sides by 2 to get x on one side, so x=
.
5. The question asks for x/3, so we can divide both sides of the equation to get
=
.
6. Simplify. We get
=
, so c is the answer.